ANALISIS PERSEPSI PENGUSAHA TERHADAP IKLIM USAHA DI KOTA MEDAN - Ernita Lestari; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2014)
This study aims to determine how perceptions ofentrepreneurs about the business climate in the city of Medan and whatis the most dominant factor as a determinant of the business climate inthe city of Medan. This research uses primary data and secondary datacollection methods of data observation, literature review, and aquestionnaire addressed to 100 employers as respondents wererandomly selected (random sampling). The analysis technique used inthis study is a descriptive analysis, which is supported by qualitativedata quantitative data processing. The results of the analysis indicatethat the perception of the entrepreneur, the business climate in the cityof Medan conducive. It is seen from the influence of government policy,political and social stability, bureaucracy and infrastructure. And fromthe research result shows that the political and social stability isconsidered the most dominant factor as a determinant of businessclimate, followed by bureaucracy and infrastructure and governmentpolicy.Keywords : Business Climate, Government Policy, Politics and SocialStability, Infrastructure, Bureaucracy